Disability: use of an independent living fund in south east London and users' views about the system of cash versus care provision. Issue 1 (February 1995) - Doyle, Y
Abstract : STUDY OBJECTIVES–To describe the uses of the Independent Living Fund (ILF) in south east London and to highlight users' views about the system of cash versus care provision for people with disabilities. DESIGN–Face to face interviews between users of the fund and an interviewer to discuss cash for care, using a structured questionnaire. SETTING–Interviews took place in the person's home. PARTICIPANTS–The database at the ILF headquarters in Nottingham of all recipients of the fund was used. People were entered into the study on an "opt-in" basis. RESULTS–Ninety five people were interviewed, of whom 72 (76%) had a modified Barthel score of less than 10. Before the ILF award, 31 (32%) people had received no community services, although it seems that social services were targeted at those living alone among the remaining 64 people. After the award, 23 of the 64 (36%) had their community services reduced or withdrawn. Sixty eight (71%) people bought a total care package with their award. Forty two people (44%) used agency care and a quarter of these had complaints about the quality of care. Seventy four (78%) overall, and 93% of those from ethnic minorities, would opt for a system of cash for care again. CONCLUSIONS–People used the ILF successfully to procure care of a type and flexibility which suited them and enabled them to live independently. Central government should reconsider wider cash for care schemes and the possibility of having both the statutory and non-statutory sectors on contract to some care users.